CrowdNote: Crowdsourcing Environment for Complex Video Annotations - Amorim, Marcello N. de; Segundo, Ricardo M. C.; Santos, Celso A. S.; Tavares, Orivaldo de L. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2017)
This paper introduces CrowdNote, a crowdsourcing environment for complex video annotations without the need for trained workers or specialists. CrowdNote is based on a cascading microtasks approach to achieve complex video annotation by aggregating and processing multiple simple annotations collected from the crowd. The approach consists of dividing complex annotation tasks into simpler and smaller microtasks and cascading them to generate a final result. Moreover, this approach allows using simple annotation tools rather than complex and expensive annotation systems. Also, it tends to avoid activities that may be tedious and time-consuming for contributors, that are the workers in crowdsourcing scenarios. The CrowdNote instance presented in this paper produces enriched videos in which all extra content added is provided, selected and positioned by the crowd.